Genetic Architecture and Selection of Chinese Cattle Revealed by Whole Genome Resequencing. (19th December 2017) - Mei, Chugang; Wang, Hongcheng; Liao, Qijun; Wang, Lizhong; Cheng, Gong; Wang, Hongbao; Zhao, Chunping; Zhao, Shancen; Song, Jiuzhou; Guang, Xuanmin; Liu, George E; Li, Anning; et al.
Abstract: The bovine genetic resources in China are diverse, but their value and potential are yet to be discovered. To determine the genetic diversity and population structure of Chinese cattle, we analyzed the whole genomes of 46 cattle from six phenotypically and geographically representative Chinese cattle breeds, together with 18 Red Angus cattle genomes, 11 Japanese black cattle genomes and taurine and indicine genomes available from previous studies. Our results showed that Chinese cattle originated from hybridization between Bos taurus and Bos indicus . Moreover, we found that the level of genetic variation in Chinese cattle depends upon the degree of indicine content. We also discovered many potential selective sweep regions associated with domestication related to breed-specific characteristics, with selective sweep regions including genes associated with coat color ( ERCC2, MC1R, ZBTB17, and MAP2K1 ), dairy traits ( NCAPG, MAPK7, FST, ITFG1, SETMAR, PAG1, CSN3, and RPL37A ), and meat production/quality traits (such as BB S2, R3HDM1, IGFBP2, IGFBP5, MYH9, MYH4, and MC5R ). These findings substantially expand the catalogue of genetic variants in cattle and reveal new insights into the evolutionary history and domestication traits of Chinese cattle.